Zbiorowiska leśne z cieszynianką wiosenną Hacquetia epipactis (Scop.) DC. na Pogórzu Cieszyńskim - Mijal, Magdalena (Leśne Prace Badawcze, 2015)
The strictly protected Hacquetia epipactis , which natural range has its north-eastern limit in the area of the Cieszyńskie Foothills, is one of the most interesting rarities of Polish flora. For one and a half centuries H. epipactis was popular with scientists resulting in a relatively high number of papers addressing this plant. Usually, however, the characteristics of sites where H. epipactis occurs have been overlooked by the researchers. The aim of this work was to fill this gap, at least partly, by determining plant associations that are preferred by this species. Based on previous phytosociological records and by implementing numerical classification methods, it was found that the Hacquetio-Fraxinetum excelsioris Marinček 1990, which is divided into two subassociations (typicum and allietosum with other variants), is the main association in which this plant species occurs. In isolated sites, mostly outside the Cieszyńskie Foothills, it also appears in fragments of Galio sylvatici-Carpinetum betuli Oberd. 1957 and Tilio cordatae-Carpinetum betuli Tracz. 1962 associations.